Abdominal accommodation induced by meal ingestion: differential responses to gastric and colonic volume loads. Issue 4 (29th January 2013) - Burri, E.; Cisternas, D.; Villoria, A.; Accarino, A.; Soldevilla, A.; Malagelada, J.‐R.; Azpiroz, F.
Abstract: Background  Using an experimental model of colonic gas infusion, we previously showed that the abdominal walls adapt to its content by an active phenomenon of abdominal accommodation. We now hypothesized that abdominal accommodation is a physiological phenomenon, and aimed to confirm that it can be induced by ingestion of a meal; a secondary aim was to determine whether the response to gut filling is region‐specific. Methods  In healthy subjects ( n  = 24) a nutrient test meal was administered until tolerated at a rate of 50 mL min −1 . Electromyographic (EMG) activity of the anterior wall (upper and lower rectus, external and internal oblique) was measured via four pairs of surface electrodes, and EMG activity of the diaphragm via intraluminal electrodes on an esophageal tube. To address the secondary aim, the response to gastric filling was compared with that induced by colonic filling (1440 mL 30 min −1 anal gas infusion; n  = 8). Key Results  Participants tolerated 927 ± 66 mL of meal (450–1500 mL). Meal ingestion induced progressive diaphragmatic relaxation (EMG reduction by 16 ± 2%; P  < 0.01) and selective contraction of the upper abdominal wall (24 ± 2% increase in activity of the upper rectus and external oblique; P  < 0.01 for both), with no significant changes in the lower rectus (4 ± 2%) or internal oblique (5 ± 3%). Colonic gas infusion induced a similar response, but with an overall contraction of the anterior wall. Conclusions & Inferences  Meal ingestion induces a metered and region‐specific response of the abdominal walls to accommodate the volume load. Abnormal abdominal accommodation could be involved in postprandial bloating.